THE ROLE OF PUBLIC ACCOUNTANTS TOWARDS THE BUSINESS PURPOSE TEST REQUIREMENTS TO CONSOLIDATE A LIMITED LIABILITY COMPANY FOR TAXATION - Muhammad Fatha Permana; Muhammad Zikriannor (Taksasila Edukasi Insani, 2025)
Restructuring of a Legal Entity, in this case a Limited Liability Company, is known in four forms, namely merger, acquisition, takeover and spin-off. The restructuring has implications for various aspects, including capital structure and share ownership, composition of management and supervisors, articles of association, and taxation. In this article, we will discuss Consolidation of the Company, and specifically regarding the implications for the taxation of Limited Liability Companies, likewise with the role of a public accountant regarding the requirements of the Business Purpose Test. The research method used in writing this article is a normative juridical research method, namely by conducting a literature study. The results of the study showed that the Government has set a policy regarding the requirements of the Business Purposes Test in order to companies consolidation and there is a public accountant role that is needed to support all the requirements of the Business Purposes Test. In addition, the results of this study also provide advice and solutions for the government, notaries and of course a company that will consolidate.Keywords: Taxation, Business Konsolidasis, Limited Liability Companies